A replacement name for Macrobrachium aemulum madhusoodani Pillai & Unnikrishnan, 2013, a junior homonym of Macrobrachium madhusoodani Unnikrishnan, Pillai & Jayachandran, 2011 (Decapoda: Palaemonidae) - Pillai, P. M.; Unnikrishnan, V. (Zootaxa, 2013)
Macrobrachium aemulum madhusoodani Pillai & Unnikrishnan (2013) was recently described based on material from the Neyyar River, Kerala, India as a new subspecies of M. aemulum (Nobili, 1906). As however, both species and subspecies names are considered part of the species-group for nomenclatorial purposes (ICZN, Art. 45.1), the name is a junior homonym of Macrobrachium madhusoodani Unnikrishnan, Pillai & Jayachandran (2011) and requires a replacement name.